2021
DOI: 10.3390/nu13020498
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hypothalamic Inflammation in Diet-Induced Obesity and Its Association with Cognitive and Mood Disorders

Abstract: Obesity is often associated with cognitive and mood disorders. Recent evidence suggests that obesity may cause hypothalamic inflammation. Our aim was to investigate the hypothesis that there is a causal link between obesity-induced hypothalamic inflammation and cognitive and mood disorders. Inflammation may influence hypothalamic inter-connections with regions important for cognition and mood, while it may cause dysregulation of the Hypothalamic-Pituitary-Adrenal (HPA) axis and influence monoaminergic systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 199 publications
3
44
0
2
Order By: Relevance
“…In this study, the incidence of depression in the obesity group was found to be higher than that in the control group, which is in line with previous studies (7,9,10,27,28). Studies have also found that the effects of obesity and depression work bidirectionally (26)(27)(28)(29) and that individuals who are obese have an 18-40% increased risk of depression (28,29). Obesity had similar odds ratios (ORs) for depression (OR 1.21-5.8) and vice versa (OR: 1.18-3.76) (26).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the incidence of depression in the obesity group was found to be higher than that in the control group, which is in line with previous studies (7,9,10,27,28). Studies have also found that the effects of obesity and depression work bidirectionally (26)(27)(28)(29) and that individuals who are obese have an 18-40% increased risk of depression (28,29). Obesity had similar odds ratios (ORs) for depression (OR 1.21-5.8) and vice versa (OR: 1.18-3.76) (26).…”
Section: Discussionsupporting
confidence: 92%
“…Obesity, along with anxiety and depressive disorders, is a major public health problem. These conditions independently affect disability and mortality rates in patients and incur a considerable socioeconomic burden; moreover, the results of several epidemiological studies, clinical trials, and recent meta-analyses support the link between mood disorders and obesity (7,9,10,26). Depression and anxiety are particularly prominent among mood disorders, not only because of their high prevalence but also because of their significant association with obesity (9,27).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, JNK inhibition restores insulin signaling in the hypothalamus of obese animals and leads to reduced caloric intake and weight loss [ 262 , 263 ]. Finally, obesity-associated hypothalamic inflammation may also lead to HPA axis dysregulation and consequently stress disorders [ 273 ].…”
Section: The Impact Of Obesity On Microglia-mediated Neuroinflammationmentioning
confidence: 99%
“…Dysregulation of the HPA axis could be a potential marker of vulnerability regarding a variety of diseases related to stress as well as neuropsychiatric disorders (121,443). In this respect, higher levels of cortisol could be directly involved in the mood changes observed in depression (111,126,444).…”
Section: Psychopathology and Salivary Cortisol And Salivary α-Amylase Measures Of Stressmentioning
confidence: 99%